Optimum salinity for growth of mangrove crab Scylla serrata seed in recirculation systems - Hastuti, Yuni Puji; Affandi, Ridwan; Safrina, Mafatih Devi; Faturrohman, Kurnia; Nurussalam, Wildan (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT One of the abiotic factors that affects the growth and the survival of crabs is salinity. The optimum salinity media will give maximum impact on mangrove crab Scylla serrata due to the osmoregulation process. This study aimed to examine the effect of salinity on the survival rate (SR) and spesific growth rate (SGR) of mangrove crab through the reaction of physiological condition. The treatments were rearing mangrove crab at the salinity medium of 15 ppt (A), 20 ppt (B), 25 ppt (C), and 30 ppt (D). Result showed that different salinity performed a significant effect (P<0.05) on the survival rate and specific growth rate of the crabs. The low level of stress, shown by the high value of total hemocyte and the low osmotic pressure, has made salinity of 25 ppt was the optimum condition for the mangrove crab rearing. Keywords: salinity, survival, specific growth rate, mangrove crab ABSTRAK Salah satu faktor abiotik yang memengaruhi pertumbuhan dan kelangsungan hidup kepiting adalah salinitas. Salinitas media optimum akan memberikan efek yang maksimal pada kepiting bakau Scylla serrata sehubungan dengan proses osmoregulasi tubuhnya. Penelitian ini bertujuan untuk menguji pengaruh salinitas pada kelangsungan hidup dan laju pertumbuhan spesifik kepiting bakau melalui reaksi kondisi fisiologis. Penelitian ini terdiri atas perlakuan salinitas media 15 ppt (A), 20 ppt (B), 25 ppt (C), dan 30 ppt (D). Hasil penelitian menunjukkan bahwa perbedaan salinitas media pemeliharaan kepiting bakau memberikan perbedaan nyata (P<0,05) pada kelangsungan hidup dan laju pertumbuhan spesifik kepiting bakau. Rendahnya tingkat stres pada salinitas 25 ppt dijelaskan dengan tingginya jumlah total hemosit dan rendahnya tekanan osmotik sehingga salinitas 25 ppt merupakan kondisi optimum bagi pemeliharaan kepiting bakau. Keywords: salinitas, kelangsungan hidup, laju pertumbuhan spesifik, kepiting bakau